Bimetallic Fe-Cu catalysts for selective hydrogenation of CO2 to olefin-rich C2+ hydrocarbons - Egamnazarova Fazilat Dustqobilovna; Akbarova Adolat Kamal's Qizi; Hasanova Sarvinoz Gairatjon Qizi; Norimov Mardonbek Abdumalik Ogli (Genius Journals, 2025)
Carbon dioxide is an important pollutant that has recently led to deterioration of the environment. In particular, CO2 can be used not only as a greenhouse gas, but also as a source of carbon for the production of a number of high-quality products, such as light olefins. Lower olefins (C2H4 and c3h6) are the main petrochemical building blocks used to produce various chemicals.
Keywords: hydrogenation; olefins; diffraction; catalyst